Bangladesh towards 21st century - Ahmad, Mohiuddin, 1952-; Community Development Library (Dhaka, Bangladesh) (Dhaka : Community Development Library, 1999)
Contributed articles; most relating to the post-1971 period.
Includes bibliographical references.
Keywords: Bangladesh -- History